Pharmacokinetics, tissue residues and efficacy of D-Tylo50/25® (tylosin-doxycycline combination) in broiler chickens - Aboubakr, Mohamed; Elbadawy, Mohamed (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Pharmacokinetic study of a commercial tylosin-doxycycline combination product (D-Tylo50/25®) was conducted in broiler chickens following intravenous (IV) and oral (PO) administration at doses of 50 mg/kgb. wt. (tylosin) and 25 mg/kg b. wt. (doxycycline). Methods: Serum drug concentrations were determined by a validated high performance liquid chromatography (HPLC) using UV detection. Results: A rapid and nearly complete absorption of both drugs with a mean PO bioavailability of 89.16% (tylosin) and 94.30% (doxycycline), prolonged elimination half-lives, and high tissue penetration with steady state volume of distribution of 6.73L/kg (tylosin) and 5.51L/kg (doxycycline) were observed. Tissue residues were studied following oral administration of each drug alone for fiveconsecutive days and blood and tissue samples were obtained for 10 days after the last dose. Residues of tylosin and doxycyclines showed that kidney, liver and lung contained highest drug residues and completely disappeared from those tissues at 5 and 6 days after the last oral dose, respectively. The efficacies of D-Tylo50/25® and other antibiotics (tiamulin and oxytetracyline) were investigated in broiler chicks experimentally infected by Mycoplasma gallisepticum. Conclusions: The pharmacokinetics of both drugs was characterized by a rapid and complete absorption, extensive tissue distribution and slow elimination. D-Tylo50/25® is more effective than tiamulin and oxytetracycline against Mycoplasma gallisepticum infection in broilers.